Motor Insurance Purchase Behaviour: A Study Of Malaysian Consumers' Preferences Of Conventional And Online Purchase Methods - Lan, Lok Bee (2004)
The purpose of the study was to empirically examine the relative factors (demography, security, website design, and convenience) that significantly influence the motor insurance consumers' choice between online purchase and face-to face service in Malaysia.